Clinical characteristics of spinning-induced rhabdomyolysis and other causes of rhabdomyolysis: a comparative study - Kashyap Shroff; Moganapriya d/o Gunasegaren; Kunzang Norbu; Eunizar Omar (Singapore Medical Journal, 2022)
Introduction: Spinning is an indoor stationary cycling programme that can cause severe rhabdomyolysis. We compared the clinical characteristics of spinning-induced exertional rhabdomyolysis (SER) with other exertional rhabdomyolysis (ER) and non-exertional rhabdomyolysis (NER). Methods: This was a retrospective observational study of adult patients presenting with rhabdomyolysis to an emergency department from August 2018 to August 2019. Patients were classified as SER, ER or NER based on chart review. We compared patient demographics, serum creatine kinase (CK), transaminase and creatinine levels, admission rates, duration of hospitalisation and treatment prescribed. Results: 62 patients were analysed. SER patients were predominantly female (77% vs. 24% vs. 26%, P < 0.01), Chinese (100% vs. 47% vs. 79%, P < 0.01) and younger (mean age 27.7 vs. 34.6 vs. 59.4 years, P < 0.01) than those with ER and NER. The SER group had the highest CK level (20,000 vs. 10,465 vs. 6,007 U/L, P < 0.01) but the lowest mean serum creatinine level (53.5 vs. 80.9 vs. 143.5 mmol/L, P < 0.01) compared to the ER and NER groups. Admission rates were the highest in SER patients (100% vs. 57% vs. 90%, P < 0.01). SER mean inpatient length of stay was longer than ER but shorter than NER patients (4.3 vs. 1.9 vs. 6.0 days, P = 0.02). Conclusion: SER is a unique form of rhabdomyolysis. Predominantly seen in young, healthy women, it often presents with extremely high CK levels. However, the prognosis is good and the rate of complication is low with fluid treatment.